112 (911) violence against healthcare workers and its results i?n Turkey - Pekince, Hatice; Duman, Ayfer Sahi N; Gürgöze, Ramazan (My University, 2022)
In this study, it was aimed to determine the situation of violence against 112 healthcare workers and the consequences of violence.This research was conducted in a descriptive\rtype. The sample of the study consists of 286 healthcare workers.A participant information form and a questionnaire on violence were used to collect data. While\r61 of the participants experienced violence once in the workplace, 115 of them stated that they experienced it many times. The majority of those who were subjected to\rviolence stated that they were subjected to verbal violence and that verbal violence was mostly in the form of swearing, insults and threats. Most of the participants state\rthat violence will be prevented by training, increasing the sentences and pre-trial detention. In the research, it is seen that there is violence against healthcare workers and\respecially verbal violence is more common. It is recommended to organize trainings to prevent violence, to increase public awareness and to increase sanctions against\rindividuals who use violence.
Keywords: Sosyal Çalışma; Sağlık Politikaları ve Hizmetleri; Hemşirelik